Causes and early effects of Organic Law 1/2009 whichreforms the Principle of universal jurisdiction in Spain - Esteve-Moltó, José Elías (Universidad Pedagógica y Tecnológica de Colombia, 2013)
According to the study of the background of the application of the principle of universal jurisdiction for the Spanish courts, an officiousness is denoted in terms of the effective recognition of human rights, all this driven by a series of legislative reforms that arises thanks on the one hand, to the necessary adjustment of the Spanish legislation to the International Criminal law, and on the other, to the political and diplomatic pressures. It was inserted the application of a principle of universal jurisdiction to solve as an exercise of justice that must at all costs be limited, by criteria such as connection to a national interest, the principle of subsidiarity and the application of a test of reasonableness. Through Organic Law 1 of the year 2009 was gave a new stage in the Spanish justice that has influenced on a large scale the international law, for its contribution to the achievement of a more just and sure world, and to strengthen international law, rather than the violence, as a common way of solving conflicts.